Performance and nutritional quality of oats for the region of Puno - Mamani Paredes, Javier (2018)
The study was carried out with the objective of determining the yield, chemical composition and nutritional value of the forage oat crop, under conditions of the Puno highlands. The samples were analyzed to determine the chemical composition of the forage using the Weende analysis method, as well as the determination of neutral detergent fiber (NDF) and acid detergent fiber (ADF) using the Van Soest method; with these results were calculated the nutritional values of digestible dry matter (DMD), the dry matter consumption (CMS), the relative value of the forage (VRF) and the net energy of lactation (ENL). The results show an average yield of 23.04 ± 3.86 t ha-1 of green matter; the average chemical composition was 27.95 ± 1.58% DM, 5.60 ± 0.67% total ash (TC), 8.67 ± 0.64% crude protein (PC), 7.99 ± 0.70% ether extract (EE), 30.77 ± 3.33 % of non-fibrous carbohydrates (CNF), 46.97 ± 3.59% of NDF, 28.78 ± 1.94% of FDA, 18.19 ± 2.56% of hemicellulose (HC), with nutritional values being 66.48 ± 1.59% of MSD, 2.63 ± 0.26% of CMS , 136.39 ± 15.85 of VRF and 1.33 ± 0.04 Mcal kg-1 MS of ENL. It is concluded that the cultivation of forage oats, is an excellent productive alternative for dairy cattle under conditions of the highlands of Puno, with great potential for yield and nutritional quality